New insights from seismic imaging over the Youanmi Terrane, Yilgarn Craton, Western Australia - Ahmadi, O.; Juhlin, Christopher; Gessner, K. (Elsevier Ltd, 2014)
©2014 The Authors. The general crustal structure of the Youanmi Terrane - a tectonic unit within the Neoarchean Yilgarn Craton - and its relationship to ore deposits are of major interest in Western Australia. To image geological structures, the Geological Survey of Western Australia in collaboration with Geoscience Australia acquired three deep crustal 2D seismic profiles over the region in 2010. In this study, we have reprocessed a 120 km long section of one of the seismic profiles, line 10GA-YU1. We reprocessed the data with focus on shallow reflections down to 2 s (about 6 km depth). A cross-dip analysis was performed to investigate the dip of the reflections in cross-line direction. The cross-dip analysis showed that there is no significant cross-dip influence, confirming that a 2D interpretation is a valid assumption for this dataset. The seismic image of the reflections was improved after applying dip-moveout correction. Finally, the reflections were migrated to their "true" locations in the subsurface. To better understand the physical properties of the subsurface, we also tried First Arrival Travel-Time Tomography. The tomography results show that low velocities correlate with shear zones and that high velocity zones are common where mineral deposits are located close to the surface.